ISSUE PRIVILEGE DALAM AL-QUR’AN (Analisis Surah Al-Fajr ayat 15-16 Perspektif Tafsir Al-Misbah) - Ilma, Nida Nur; Hermanto, Edi; Saputra, M. Irwanda; Hidayati, Rahmah; -, Sahrul (Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
The issue of privilege has become a hot topic of debate in this modern era, as it has been misinterpreted to benefit some and harm others. This issue is important because it creates feelings of insecurity and ungratefulness in individuals. This research uses a qualitative method with content analysis of trends and standards in social media to understand more about the concept of privilege and its impact on society. This research also takes as its basis QS Al Fajr verse 15 and 16 through tafsir Al Misbah, which emphasizes the importance of understanding the privileges of each individual. The results show that the concept of privilege if viewed in the wrong way can lead to feelings of insecurity and ungratefulness in individuals. However, by understanding that each individual has their own privileges given by Allah SWT, it is hoped that individuals can overcome feelings of insecurity and ungratefulness, and develop an attitude of gratitude and appreciation for what Allah has given